Jurnal Kata: juxtaposition of women, culture, and nature in alice walkers possessing the secret of joy - Pedram lalbakhsg, Ali khoshnood; Farzane gholami (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
the presetn paper focuses on the tradition of womens circumsicion in the african tribe of olinkan in alice walkers possessing the secret of joy